2021
DOI: 10.18632/aging.203150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of samul-tang on female fertility via RAS signaling pathway in ovaries of aged mice

Abstract: Samul-tang (SM), a traditional herbal medicine, is used to treat age-related human conditions, such as infertility and menstrual irregularities. The mechanism underlying the role of SM in ovary function needs elucidation. In this study, the influence of SM administration on the ovarian reserve of aged mice was investigated. Female BALB/c mice (8 and 40 weeks-old) were administered with distilled water (young or old group) or SM for 4 weeks. SM administration prevented age-related ovarian follicle loss in mice.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…SWT administration also restored miR-223-3p, which could interact with embryo implantation-related genes (Hal, Acp5) in the uterus of aged mice (97). This transcriptome analysis result was consistent with the phenotypic findings of the protective effect of SWT on the increase of ovarian reserve, ovulated mature oocytes, and pregnancy rate in aged mice (96,97). Tao-Hong-Si-Wu Decoction (THSWD), a traditional herbal medicine, is composed of six herbs (Prunus persica, Carthamus tinctorius, Rehmannia glutinosa, Angelica sinensis, Paeonia lactiflora, and Ligustium chuanxiong).…”
Section: Transcriptome-based Elucidation Of Molecular Target And/or M...supporting
confidence: 85%
See 3 more Smart Citations
“…SWT administration also restored miR-223-3p, which could interact with embryo implantation-related genes (Hal, Acp5) in the uterus of aged mice (97). This transcriptome analysis result was consistent with the phenotypic findings of the protective effect of SWT on the increase of ovarian reserve, ovulated mature oocytes, and pregnancy rate in aged mice (96,97). Tao-Hong-Si-Wu Decoction (THSWD), a traditional herbal medicine, is composed of six herbs (Prunus persica, Carthamus tinctorius, Rehmannia glutinosa, Angelica sinensis, Paeonia lactiflora, and Ligustium chuanxiong).…”
Section: Transcriptome-based Elucidation Of Molecular Target And/or M...supporting
confidence: 85%
“…Si-Wu-Tang (SWT) (Samul-tang in Korean, Shimotsu-to in Japanese) is one of the most popular herbal prescriptions consisting of four herbs including Paeonia Radix, Ligusticum Rhizoma, Rehmannia Radix, and Angelica Radix at a 1:1:1:1 ratio. It has been clinically applied for centuries in Asia to treat symptoms of hematological disorders such as anemia, menstrual irregularities, dysmenorrhea, and menopausal syndrome (89)(90)(91)(92)(93)(94)(95)(96)(97). In recent years, an increasing number of studies have elucidated the MOA of SWT by analyzing SWT-induced changes in gene expression.…”
Section: Transcriptome-based Elucidation Of Molecular Target And/or M...mentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we reported that Samul-tang (SM), comprising Paeonia lactiflora, Ligusticum striatum, Rehmannia glutinosa , and Angelica giga , improves implantation potential in aged mice. 13 This herbal preparation has been traditionally used to manage infertility symptoms in humans and rodent models. 14 , 15 In this study, we explored uterine transcriptomic changes in the metestrus phase of the estrous cycle in the aged and hormonally stimulated uteri of mice.…”
Section: Introductionmentioning
confidence: 99%